The Influence of Board Structure and Ownership Concentration on GRI Reporting - de Mascena, Keysa Manuela Cunha; Barakat, Simone R.; Isabella, Giuliana; Fischmann, Adalberto A. (Review of Business Management, 2020)
Purpose – The purpose of this paper is to investigate the relationship between corporate governance structure and GRI reporting. More specifically, the study seeks to analyse board independence, board size and ownership concentration and their relationships with GRI reporting. Design/methodology/approach – The hypotheses of the study were tested in a sample of 287 Brazilian companies listed on the B3, the Brazilian stock exchange, using logistic regression models. Data from 2013 were collected from the Econoinfo and GRI databases. Findings –The findings show that there is a positive relationship between both board independence and GRI reporting and board size and GRI reporting, and a neutral relationship between ownership concentration and GRI reporting. These results indicate that the corporate governance structure influences a company’s decision to engage in social issue and stakeholders’ relationship activities. Originality/value – The contribution of this study is it presents theoretical arguments and empirical evidence regarding the influence of corporate governance structure on CSD beyond the Anglo-Saxon context. The results show that good corporate governance practices cannot be generalized to different contexts.